2020
DOI: 10.20485/jsaeijae.11.2_40
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acceptability of Adaptive Proactive Braking Intervention System Based on Risk Map for Elderly Drivers

Abstract: This study aims to confirm the usefulness of adaptation of proactive braking intervention systems to the risk level of the driving environment for improving the reactive factors of acceptability. First, we develop prototypes of adaptive proactive braking intervention systems around non-signalized intersections on community roads. Then, to confirm the effectiveness of adaptation, we conduct user tests, in which 45 elderly drivers participate, on public roads. From comparisons between constant setting and adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In the previous studies [14,16,17], we confirmed that the comprehensive factors were positively evaluated; further, it led to the positive evaluation of total system acceptance. However, such evaluations regarding each factor were conducted in the limited preparation stage conditions.…”
Section: Acceptability Evaluationsupporting
confidence: 75%
See 3 more Smart Citations
“…In the previous studies [14,16,17], we confirmed that the comprehensive factors were positively evaluated; further, it led to the positive evaluation of total system acceptance. However, such evaluations regarding each factor were conducted in the limited preparation stage conditions.…”
Section: Acceptability Evaluationsupporting
confidence: 75%
“…However, because we did not know how the experimental participants would behave and interact with the proposed system, we conducted the Pre-FOT on the private test course for safety. After that, we conducted Pilot FOTs [9,17] for confirming the unique problems on public roads. The advanced points from Pre-FOTs were that evaluations were conducted on public roads.…”
Section: Preparation Of Data Collection For Evaluating Proactive Braking Intervention Systemmentioning
confidence: 99%
See 2 more Smart Citations